2022
DOI: 10.7554/elife.73557
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the CaMKII-Sarm1-ASK1-p38 MAP kinase pathway protects against axon degeneration caused by loss of mitochondria

Abstract: Mitochondrial defects are tightly linked to axon degeneration, yet the underlying cellular mechanisms remain poorly understood. In Caenorhabditis elegans, PVQ axons that lack mitochondria degenerate spontaneously with age. Using an unbiased genetic screen, we found that cell-specific activation of CaMKII/UNC-43 suppresses axon degeneration due to loss of mitochondria. Unexpectedly, CaMKII/UNC-43 activates the conserved Sarm1/TIR-1-ASK1/NSY-1-p38 MAPK pathway and eventually the transcription factor CEBP-1 to pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 118 publications
0
18
0
Order By: Relevance
“…Our results in primary DRG neurons suggest that GSSSG prevents not only mitochondria fragmentation (or fission) induced by paclitaxel, but also loss of mitochondria in neural axons. As reported previously, redox balance and glutathione oxidation in neural axons partly regulate mitochondrial transportation from cell body to axon [ 40 ], and loss of axonal mitochondria results in axonal degeneration [ 41 ] and neuropathy [ 42 ]. Our observations support that GSSSG attenuates PIPN via protecting mitochondria by regulating redox balance in peripheral neurons.…”
Section: Discussionmentioning
confidence: 96%
“…Our results in primary DRG neurons suggest that GSSSG prevents not only mitochondria fragmentation (or fission) induced by paclitaxel, but also loss of mitochondria in neural axons. As reported previously, redox balance and glutathione oxidation in neural axons partly regulate mitochondrial transportation from cell body to axon [ 40 ], and loss of axonal mitochondria results in axonal degeneration [ 41 ] and neuropathy [ 42 ]. Our observations support that GSSSG attenuates PIPN via protecting mitochondria by regulating redox balance in peripheral neurons.…”
Section: Discussionmentioning
confidence: 96%
“…Intriguingly, this rescue is specific to PMK-3 signaling and not PMK-1 signaling (Ding et al 2022). In the current study, we identified pmk-1-dependent signaling for key gene expression programs to support sensory neuronal integrity during aging in the absence of a stressor.…”
Section: Discussionmentioning
confidence: 97%
“…Neurodegeneration as a result of expressing mutant TDP-43 or FUS is driven by an innate immune response dependent on PMK-1 signaling (Veriepe et al 2015). In contrast, loss of mitochondria resulting in neurodegeneration is alleviated by activating CaMKII (UNC-43) signaling leading to PMK-3 activation and ultimately CEBP (Ding et al 2022). Intriguingly, this rescue is specific to PMK-3 signaling and not PMK-1 signaling (Ding et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In day 1 adults, genes regulated by the transcription factor CEBP-1 were upregulated. In C. elegans , CEBP-1 has been shown to activate a gene expression program that protects axons from degeneration [ 56 ]. Genes regulated by NHR-6, a transcription factor expressed in chemosensory neurons found to be important for functional plasticity [ 57 ], were enriched in day 6 adults.…”
Section: Discussionmentioning
confidence: 99%